High-concentration topical capsaicin in the management of refractory neuropathic pain in patients with neurofibromatosis type 1: a case series. (4th May 2018) - Bardo-Brouard, P.; Luizard, C.; Valeyrie-Allanore, L.; Goujon, C.; Do, B.; Colin, A.; Wolkenstein, P.; Paul, M.
Abstract: Aim: The aim of this case series was to report the use of 8% topical capsaicin patch (marketed under the trade name Qutenza ® ) a in the management of refractory neuropathic pain (NP) in adult patients with type 1 neurofibromatosis (NF1). Methods: Capsaicin has been suggested for NF1 patients suffering from refractory peripheral NP despite several years of analgesic treatments. The patch was applied for 60 minutes on the painful area, with tolerability control (blood pressure, intensity of pain and dermal reaction). The evaluation was done at the beginning of treatment and during the 2 months following the first treatment (phone calls at weeks 1, 2, 4 and 8). The primary efficacy criterion was the response rate: a patient was considered to be responding if he or she reported an average relief ≥30% at the time of the follow-up calls. The secondary criteria were: interference scores (QCD), Patient Global Impression of Change (PGIC) and overall treatment satisfaction, self-reported by the patient. Results: Eight patients (5 females/3 males, 41.8 ± 8.2 years of age) received a first treatment with capsaicin. Patients had pre-existing pain for 6.6 years (±6.0) and were currently receiving an average of 6.1 (±3.9) different analgesics. The response rate was 37.5%. The three responders felt globally improved and satisfied, with the improvement in overall condition as interference scores decreased. Apart from the expected local reactions, the treatment was not accompanied by systemic side effects. Conclusions: As suggested in this case series, capsaicin provided pain relief in certain NF1 patients with resistant NP. The response rate is that expected in multi-line refractory NP. A significant benefit on the overall condition of some patients was observed. In addition, this topical treatment is administered every 3 months without systemic effects. This study is limited by the small number of patients, but was intended to describe a new and well tolerated alternative treatment.